Análisis de factibilidad técnica y económica para la instalación de transformadores de potencial con alimentación para servicios auxiliares en subestaciones de seccionamiento - Bustamante Sarabia, Luis Francisco (2022)
In the present investigation, a comparison was made between the economic costs and the technical requirements to feed the auxiliary services of a sectioning substation; The case study has been applied to the La Concordia sectioning substation, in such a way that the field investigation allowed obtaining real information to verify the implementation of new technologies. The systems that have been analyzed start from a medium voltage feeder connected to the 13.8 kV network of the distribution company CNEL, which is later connected to a 225 kVA three-phase PadMounted type transformer to feed the auxiliary services of the S/E of sectioning La Concordia, in comparison with the implementation of a voltage transformer with power winding for auxiliary services, whose specific function is to maintain two windings for measurement and protection, which is the inherent work of a PT; but it also adds a winding that allows direct low voltage voltage to be taken from the high voltage line, with the aim of feeding specific loads, in this case, applied to the auxiliary services of a sectioning substation.